Stability, Electronic and Optical Properties of the Boron Nitride Cage (B 47 N 53 ) from Quantum Mechanical Calculations - Cardenas-Jiron, G; Borges-Martinez, M (Elsevier B.V., 2019)
The structural, electronic and optical properties of an isomer proposed for the boron nitride cage (BN; BxNy; x = 47, y = 53) in the gas phase were carried out by means of DFT calculations. The results of the quantum simulations indicate there is not magnetism associated to the stable structure with neutral charge. However, the system exhibits a high cohesion energy (−6.08 eV/atom), this feature is relating to its high chemical stability. The quantum descriptors indicate a moderate polarity, low chemical reactivity as well as low work function for this nano-cage. This system has electronic behavior like-conductor, opposite to others BN nanostructures. On the other hand, the electronic absorption spectrum was obtained using six density functionals under the formalism of the time-dependent DFT and show a good agreement with the experimental data, these calculations reveal a strong absorption band at ≈ 260 nm in the UV region. The natural transition orbitals suggest an intramolecular charge transfer inside of BN cage, and the laplacian of the electron density evaluated in the bond critical points confirms that the cage is stabilized by the presence of homo-nuclear bonds B–B and N–N. © 2019 Elsevier B.V.